Preliminary observations regarding the effect of daily drip irrigation by pulsing on the optimisation of almond tree management in sandy soils in Australia - Bennett C. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
This study aims to investigate and quantify the advantages of optimizing water usage per ton of almonds produced. This work seeks to adapt previous findings by Assaf et al. in apples and stone fruit in Israel to conditions in Australian commercial almond orchards. These include sandy to sandy loam infertile soils, calcareous subsoils and summer daily temperatures of 30 degrees C to 46 degrees C. Our initial findings appear to concur with Assaf, who found both soil aeration and wetted soil profile to be around 60 per cent greater using pulse irrigation techniques. Lateral distribution of the water was found to be up to 2.5 m.This paper outlines preliminary observations regarding the importance of daily pulse irrigation in maximizing the wetted soil volume, developing extensive and healthy root systems and maximising irrigation efficiency. Benefits were also observed in the allied management areas of nutrition and canopy management, resulting in a significant improvement in cropping performance.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)